Bryggium. - Stadshallen Brugge; Traen, Fernand; d'Arschot, Philippe (Brugge : Stad Brugge, 1966)
Van Anderlecht, Englebert ; Benrath, Frédéric ; Bert, Kari ; Bertrand, Gaston ; Brande, Frans Van Den ; Buchheister, Carl ; Claus, Hugo ; D'Haese, Roel ; Dova, Gianni ; Dries, Jan ; Drybergh, Charles ; Gillet, Roger Edgar ; Grazebrook, Romarin ; Jorn, Asger ; Largot, Serge ; Lerin, Fernando ; Martin, Remo ; Michaux, Henri ; Mortier, Antoine ; Raveel, Roger ; Reinhoud ; Serpan, Iaroslav ; Servranckx, Victor ; Van Severen, Dan ; Vandercam, Serge ; de Velde, Wim Van ; Wouters, Roger ; Wyckaert, Maurice
biografie
Bryggium : catalogus, Stadshallen, Brugge, 11.6 - 4.9.1966
Nederlands
Nederlands & Frans & Engels & Duits
boek